INFLUENCE OF NITROGEN CONTENT ON RICE LEAF SHEATHS ON SHEATH BLIGHT DEVELOPMENT - Schurt, Daniel; duarte, Henrique; Rodrigues, Fabricio; Lopes, Ueder; duarte, Henrique (Scientia Agraria, 2017)
This study aimed to evaluate the effect of different leaf content nitrogen (N) on development of sheath blight (Rhizoctonia solani) in rice cultivars BR-IRGA 409 and Labelle grown in nutrient solution containing 0, 50 and 100 mM of N. Sheath blight progress on inoculated leaf sheaths was evaluated by measuring the relative lesion length at 48, 72, 96 and 120 hours after inoculation and this dates used to calculate the area under relative lesion length progress curve (AURLLPC). The N concentration increased by 100 and 122% in cultivars Labelle and BR-IRGA 409, respectively, as the N rates increased from 0 to 100 mM. The AURLLPC increased by 17.6 and 23.6% in the cultivars Labelle and BR-IRGA 409, respectively, as the N rates in the nutrient solution increased. Our data suggest that high concentration of N on rice leaves favor sheath blight development Labelle and BR-IRGA 409 and suggests exist a mechanisms involved extends beyond changing the microclimate between plants.